Аналіз впливу стабілізації вихідних властивостей агломерату на фізико-хімічні процеси в характерних зонах доменної печі - Мішалкін, А.П.; Маловік, Д.В.; Чистяков, В.Г.; Петренко, В.О. (Physico-technological Institute of Metals and Alloys, 2025)
The article investigates the stabilization of the physicochemical properties of iron ore sinter and pellets, as the main components of the blast furnace charge, on physicochemical processes in the characteristic zones of the blast furnace, which is an urgent problem for further improvement of the technology of smelting cast iron. Obtaining high-quality sinter is a complex task, and its solution is based on the stabilization of its initial properties. It is substantiated that the most effective in terms of impact on the results of the process are the increase in mechanical strength, thermal, physicochemical and granulometric stability of the sinter, which affect the conditions and behavior of the components in the characteristic zones under the corresponding conditions of the blast furnace. The stabilization of the physicochemical characteristics of the sinter is investigated as one of the important factors for ensuring the most rational use of its physicochemical potential when passing through the high-temperature zones of the blast furnace. The key rheological properties of granular flows of the blast furnace charge have been determined, which is important in terms of substantiating effective loading methods and technical solutions for the distribution of charge components in the blast furnace. The influence of the fractional composition of the charge and the ratio of its main components on gas-dynamic conditions has been investigated, especially in the dry zone, the most extensive zone of physicochemical transformations of the blast furnace, which is one of the key factors determining the efficiency of the blast furnace process. The study used theoretical and analytical methods with an emphasis on the physicochemical component, which include analysis, generalization and interpretation of the results obtained in the context of the correspondence of theoretical concepts and provisions to practical results. Consistent ideas about the peculiarities of the behavior of charge components in the blast furnace have been obtained. Comparison of such data obtained by different researchers can be used in the future to identify the relevant parameters. The latter, as indicators that determine the conditions for the rational use of effects, the source of which is the interaction of the useful properties of the physicochemical potential of the initial charge and external factors, will allow us to determine reliable interpretations of phenomena, predict the results and indicators of the blast furnace process. They will also become the basis for scientific substantiation of approaches to the selection of effective methods for stabilizing the properties of the sinter with the establishment of reliable relationships between the methods of loading, distribution of the components of the initial charge and gas-dynamic conditions in the furnace. It is substantiated that to ensure the stability of the blast furnace process, it is necessary to ensure the constancy of the granulometric, chemical composition, mineralogy of the initial iron ore materials (sinter and pellets), coke, as well as high quality and uniformity of the sinter. Systematic control and current regulation of these parameters is the basis for further optimization of the blast furnace process, rational in terms of specific costs of raw materials and energy resources and effective in terms of the results of implementing the properties of its initial physicochemical potential. It has been proven that a stabilized sinter, in particular in terms of size, porosity, strength, and chemical composition, contributes to increasing furnace productivity, reducing fuel consumption, and improving the quality of cast iron by optimizing physicochemical processes in the blast furnace due to the stability of the flow of gases, that are energy carriers, reducing temperature fluctuations in characteristic zones of the furnace, improving the conditions for the reduction of iron oxides, reducing dust formation and iron losses, and saving coke. Generalization of the research results will allow us to clarify the physicochemical features of the interaction of granular flow components in variable blast furnace conditions.